Desire for Success Awakens: Proof of Competence Restoration in a Non-competitive Environment - Meng, Liang; Pei, Guanxiong; Zhang, Yupei; Jin, Jia (Frontiers in Neuroscience, 2021)
In this study, we explored the effect of competition outcome on one’s autonomous motivation in a subsequent non-competitive environment. Participants were randomly assigned to two treatment groups (a winning group and a losing group) and a control group. The experiment lasted for three sessions. Participants in the control group completed a single-player stop-watch (SW) task all along, while those in both treatment groups worked on an online SW task and competed for monetary rewards during Session 2 only. For participants in the losing group, more pronounced feedback-related negativity difference wave was observed in Session 3 compared with Session 1, suggesting enhanced autonomous motivation in Session 3. Such a pattern was observed in neither the winning group nor the control group. These results suggested that failure in a prior competition would activate one’s competence restoration in a subsequent non-competitive environment, which advanced understanding of the competence restorative process and helped clarify the dynamics between competition and human motivation.